GROWTH AND INEQUALITY: THE ROLE OF POLITICAL ECONOMY - Carranza Ugarte, Luis (2023)
There is a broad debate in the economic literature about the relationship between growth and inequality. The objective of the work is to show how policy decisions affect the interrelationships between both variables but emphasizing the preferences of the agents and not the production function, as has usually been treated in the literature. Therefore, in this paper we present a model that includes externalities on the consumption side, inquiring the impact of economic policies on growth and inequality, finding multiple equilibria with different dynamics.